Design, Synthesis, Characterization and Preliminary Anticancer Study for Methotrexate Silibinin Conjugates - A. Nadhum, Shams; H. Mohammed, Mohammed (Iraqi Journal of Pharmaceutical Sciences, 2017)
The spectrum of clinical efficacy of Methotrexate (MTX) is broad in that MTX is used in the treatment of certain cancers, severe psoriasis and rheumatoid arthritis.Various mechanisms by which cancer cells grown in tissue culture become resistant to anticancer drugs. The use of multiple drugs with different mechanisms of entry into cells and different cellular targets allows for effective chemotherapy and high cure rates. In an efforts to develop effective strategies that increase the therapeutic potential of anticancer drugs with less systemic toxicity ,are being directed towards the investigation of dietary supplements and other phytotherapeutic agents for their synergistic efficacy in combination with anticancer drugs. A promising approach to improve the cancer cell selectivity of methotrexate is the chemical transformation into reversible derivatives which convert the conjugate to the parent drug by virtue of enzyme within cancer tissue. The present study includes the synthesis of two derivatives of methotrexate which are :-Schiff base methotrexate-silibinin conjugate ( compound 5), and Methotrexate-silibinin conjugate (compound 6).The synthesis of the target compounds was accomplished following multistep reaction procedures. The chemical reactions were followed up and purity of the products was checked by TLC. The structures of the final compounds and their intermediates were characterized and identified by their melting points, infrared spectroscopy, 1H-NMR and elemental microanalysis(C H N S).The anticancer activity of these compounds was investigated by HEP-2 cell line(Larynx carcinoma), which showed that compounds 5 and 6 have the higher activity than methotrexate or silibinin alone.These are promising data for the discovery of new anticancer agents in future. These compounds may deliver the parent drug selectively into the cancer cells to be hydrolyzed by enzymes that are elevated in tumor tissues compared with normal tissues .Keywords: Methotrexate, Silibinin, Cancer treatment resistance, Folate receptor, Cancer cell targeting.